Clinical profile of pediatric patients with vesicoureteral reflux (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Vesicoureteral reflux (VUR), a common pediatric urologic anomaly, predisposes children to recurrent urinary tract infections and renal scarring. Clinical presentation data from resource-limited South Asian settings remain sparse. Objective: To describe the clinical profile of pediatric patients with vesicoureteral reflux at a tertiary care hospital in Bangladesh. Methods: This prospective cohort study was conducted at Bangladesh Medical University, Dhaka, Bangladesh, from January 2024 to December 2025. Eighty-seven children aged